2020
DOI: 10.3389/fphys.2020.553563
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Related Genes of Muscle Growth and Exploring the Functions by Compensatory Growth in Mandarin Fish (Siniperca chuatsi)

Abstract: How organisms display many different biochemical, physiological processes through genes expression and regulatory mechanisms affecting muscle growth is a central issue in growth and development. In Siniperca chuatsi, the growth-related genes and underlying relevant mechanisms are poorly understood, especially for difference of body sizes and compensatory growth performance. Muscle from 3-month old individuals of different sizes was used for transcriptome analysis. Results showed that 8,942 different expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Gene expression changes caused by starvation and refeeding affect muscle metabolism and growth rate and can sometimes impair muscle growth (Hornick et al 2000;Hagen et al 2009). In teleosts, the preservation of skeletal muscle development and growth depends mainly on nutrient availability, which modulates the GH/IGF1 axis (Reinecke et al 2005;Liu et al 2020) that regulates the metabolism of different nutrients, synthesis of protein in muscle, and other tissue growth (Butler and Le Roith 2001). The endocrine activity of GH includes two major pathways: the direct one mediated by binding of GH to its receptor (GHR) and the indirect pathway via induction of IGF-1 secretion that promotes different biological activities (Canosa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression changes caused by starvation and refeeding affect muscle metabolism and growth rate and can sometimes impair muscle growth (Hornick et al 2000;Hagen et al 2009). In teleosts, the preservation of skeletal muscle development and growth depends mainly on nutrient availability, which modulates the GH/IGF1 axis (Reinecke et al 2005;Liu et al 2020) that regulates the metabolism of different nutrients, synthesis of protein in muscle, and other tissue growth (Butler and Le Roith 2001). The endocrine activity of GH includes two major pathways: the direct one mediated by binding of GH to its receptor (GHR) and the indirect pathway via induction of IGF-1 secretion that promotes different biological activities (Canosa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among these down-regulated mRNAs, a total of 52 mRNAs, including mapk15, igfbp2, creb5, adamts16, tnfsf12, fgf16, tgfbi, capn9, myf5, fgf13, fgf14, myod1, map2k4, map3k2, cdkn3, asb15 are associated with muscle growth which suggests a massive change in muscle development pattern at molecular levels. A recent approach to finding molecular differences in muscle growth of Chinese perch ( Siniperca chuatsi ) and large-scale loach ( Paramisgurnus dabryanus ) reported 8942 and 320 DE mRNAs between large and small individuals, respectively [ 28 , 29 ]. Our results are in line with these findings that describe the significant impact of myf5, igf, and igfbp in the accumulation of muscle mass [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spliceosome recognizes splicing signals located both at exon-intron boundaries and numerous cis- regulatory sequences that act as splicing enhancers or silencers [ 36 ]. It has been shown that spliceosomal complex-dependent alternative splicing produces multiple mRNA variants in muscle [ 28 ]. The spliceo-some is also involved in circRNA production in addition to its role in constitutive and alternative linear RNA splicing [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morphology traits such as a total number of fibers and myofiber diameter are major determinant factors of muscle mass as well as meat quality (38). According to a prior study, myofiber hypertrophy and hyperplasia, which increase in myofiber diameter and quantity, respectively, are the key determinants of myofiber growth (39). The myofiber diameters in fish fed 160 mg/kg C-I20 and FM diets-feed All values are presented as mean Âą SD (twelve fish flesh samples per group were collected and four flesh samples were mixed as a pooled sample.…”
Section: Discussionmentioning
confidence: 99%